Immediate effects of extracorporeal radial pressure wave therapy on dystonia, static plantar pressure distribution, and balance in patients with Parkinson’s disease - Xu, Zhiqin; Huang, Xin; Liu, Qingqing; Peng, Bo; Zhou, Lingxiang; Dong, Xinghua; Dai, Guangyan; Zhu, Xiaoxia; Weng, Zepeng; Lei, Di; Chen, Xi (Frontiers in Aging Neuroscience, 2025)
BackgroundExtracorporeal radial pressure wave therapy (ERPWT) has emerged as a potential non-invasive treatment for various musculoskeletal and neurological disorders. This study investigates the immediate effects of ERPWT on dystonia, static plantar pressure distribution, and balance in patients with Parkinson’s disease (PD).MethodsThirteen participants with PD were recruited from the Department of Rehabilitation Medicine at the First Affiliated Hospital of Sun Yat-sen University. After obtaining informed consent, clinical information was recorded, and measurements of lower limb muscle tone, stiffness, and elasticity, as well as static plantar pressure distribution and center of pressure (COP), were measured. Participants subsequently received a single session of ERPWT administered to the bilateral plantar fascia. Following ERPWT, participants were re-evaluated immediately after treatment.ResultsAfter ERPWT, significant decreases were observed in muscle tone, stiffness, and elasticity of the achilles tendon on the more PD-affected side and the anterior aspect of the planta on both feet (p < 0.05). Additionally, significant reductions in COP measures were noted post-treatment (p < 0.001). However, no significant changes were found in muscle tone, stiffness, and elasticity of the achilles tendon on the less PD-affected side or in the anterior tibialis and gastrocnemius. Furthermore, there were no significant changes in static plantar pressure distribution (p > 0.05).ConclusionThese findings indicate that a single session of ERPWT applied to the bilateral planta fascia can yield immediate beneficial effects in reducing dystonia symptoms and improving balance in patients with Parkinson’s disease. This therapy may serve as an adjunctive treatment to address motor symptoms in this population. Further research is warranted to explore the long-term effects of ERPWT and its mechanisms of action in PD patients.